1981
DOI: 10.1083/jcb.91.2.545
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of proteins across the endoplasmic reticulum. I. Signal recognition protein (SRP) binds to in-vitro-assembled polysomes synthesizing secretory protein.

Abstract: An 11S protein composed of six polypeptide chains was previously purified from a salt extract of dog pancreas microsomal membranes and shown to be required for translocation of nascent secretory protein across the microsomal membrane (Walter and Blobel 1980 Proc . Natl . Acad . Sci. U. S. A. 77 :7112-7116) . This 11S protein, termed signal recognition protein (SRP), has been shown here (a) to inhibit translation in the wheat germ cell-free system selectivity of mRNA for secretory protein (bovine preprolactin)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
282
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 618 publications
(290 citation statements)
references
References 14 publications
4
282
0
1
Order By: Relevance
“…The fact that SRP14 was cross-linked to ribosomal components in all samples was consistent with the previous observations that SRP could bind directly to ribosomes in a signal sequence-and nascent chain-independent fashion (25,(29)(30)(31). Moreover, it demonstrated that the Alu domain was already in close proximity to the ribosome in the absence of elongation arrest.…”
Section: The Alu Domain Has Conserved Binding Sites On Thesupporting
confidence: 91%
“…The fact that SRP14 was cross-linked to ribosomal components in all samples was consistent with the previous observations that SRP could bind directly to ribosomes in a signal sequence-and nascent chain-independent fashion (25,(29)(30)(31). Moreover, it demonstrated that the Alu domain was already in close proximity to the ribosome in the absence of elongation arrest.…”
Section: The Alu Domain Has Conserved Binding Sites On Thesupporting
confidence: 91%
“…First, the cytosolic and chloroplast SRPs recognize significantly different forms of "cargo." The cytosolic SRP interacts with ribosome • nascent chain complexes bearing SRP signal sequences (Walter et al, 1981;Schaffitzel et al, 2006), whereas the cpSRP binds to its substrates, LHCPs, as fully translated proteins (Tu et al, 2000;Delille et al, 2000). Second, the cpSRP lacks the SRP RNA, which is otherwise universally conserved in all the other SRP pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Cotranslational protein targeting begins with recognition of the cargo-ribosomes translating nascent polypeptides containing signal sequences-by the SRP (Walter et al, 1981). The cargo is brought to the vicinity of the target membrane via the interaction between the SRP and SRP receptor (FtsY in bacteria) (Gilmore et al, 1982a).…”
Section: Introductionmentioning
confidence: 99%
“…In eukaryotes, mRNA encoding secreted and membrane proteins can be targeted to the ER co-translationally by the signal recognition particle 1,2 and can be maintained on the ER via the direct interactions between ribosomes and translocons during the translation 3,4 . However, whether mRNAs can be targeted and maintained on the ER independent of either ribosomes or translation was unclear until very recently.…”
Section: Introductionmentioning
confidence: 99%